SUPPORTING APPLICANTS FOR THE ACL/AOA EVIDENCE-BASED REVIEW PROCESS. (11th November 2018) - Steinman, L E; Haynes, P; Denison, P E; Hughes, S; Weisner, S E
Abstract: The National Council on Aging is partnering with the Evidence-Based Leadership Council (EBLC) to support program developers/administrators to enhance research and/or delivery systems and supports. EBLC is a collaborative of organizations who develop and administer EBPs, and who have successfully implemented and sustained multiple programs. We work with NCOA, ACL/AoA, and other partners to support organizations develop, deliver, and scale EBPs. With support from ACL/AoA and NCOA, EBLC is providing free technical assistance to applicants who do not met EBP criteria to help support further EBP development. Applicants are given detailed feedback from reviewers about areas that need to be strengthened: research methods (e.g., sample size, measures, study duration, design) or dissemination and implementation infrastructure (e.g., training and implementation manuals, quality assurance checklists, data management tools, tracking program locations). Our overall aim is to expand EBPs available to promote healthy aging and manage chronic diseases across diverse settings and populations.